IMPACT OF DRIVING STYLE ON THE EXHAUST EMISSION OF A DIESEL MULTIPLE UNIT - Andrzejewski, Maciej; FUC, PAWEL; Gallas, Dawid; ZIÓLKOWSKI, ANDRZEJ; DASZKIEWICZ, PAWEL (WIT Transactions on the Built Environment, 2020)
This paper considers aspects regarding exhaust emissions from vehicles, the reduction of which is one of the main trends of current worldwide development efforts. These efforts resulted in numerous legal tools being created to tackle the problem of toxic gas emissions and global warming. These tools include emission limits and type approval procedures. Such norms for rail vehicles are simplistic and fail to provide a reliable method of assessing the real exhaust emission from rail vehicles operating on the tracks. Hence, PEMS (portable emission measurement system) type apparatus was used to perform measurements of exhaust emissions of a diesel multiple unit designed for short–mid range passenger transport in real operating conditions. The vehicle tested belonged to a widely and commonly used group of passenger vehicles, and the testing methods were similar to current RDE (real driving emissions) test requirements for road vehicles. The selected vehicle was powered by an internal combustion engine in which ecological and economic properties depend on the operating ranges and parameters used. These types of train lines are characterized by frequent stops at stations, which confirms the need to investigate this subject. The vehicle exhaust emissions were measured for different driving styles, regular driving style typical for the driver and a drive more closely in line with the concepts of eco-driving, with reduced maximum acceleration values. Since most previous studies on the eco-driving principles used road vehicles for testing, this resulted in a gap in knowledge in this field regarding rail vehicles. The aim of the paper is to assess the impact of the choice of driving style on the exhaust emission values of a selected passenger rail vehicle.